On Soulsring Worlds : narrative complexity, digital communities, and interpretation in Dark Souls and Elden Ring - Caracciolo, Marco (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"The first book-length study devoted to FromSoftware games, On Soulsring Worlds explores how the Dark Souls series and Elden Ring are able to reconcile extreme difficulty in both gameplay and narrative with broad appeal. Arguing that the games are strategically positioned in relation to contemporary audiences and designed to tap into the new forms of interpretation afforded by digital media, the author situates the games vis-à-vis a number of current debates, including the posthuman and the ethics of gameplay. The book delivers an object lesson on the value of narrative (and) complexity in digital play and in the interpretive practices it gives rise to. Cross-fertilizing narrative theory, game studies, and nonhuman-oriented philosophy, this book will appeal to students and scholars of game studies, media studies, narratology and video game ethnography"--
Keywords: Dark souls (Video game); Elden Ring (Video game); Video games -- Design; Narration (Rhetoric) -- Philosophy; Video games -- Moral and ethical aspects; GAMES / Video & Electronic; SOCIAL SCIENCE / Media Studies